Anticipated Reductions in Tax Rates and Earning Management of Listed Companies: Evidence from China. (5th October 2021) - Bai, Mo; Song, Dandan; Li, Helin
Abstract : The effects of tax rate changes on corporations' earning management are not fully understood. As a transitional economy, China has listed companies with different ownership and special regulatory rules. We explore under the expectation of tax reduction whether there are differences in the way and degree of earnings management implemented by different types of companies. Our study shows that firms under the anticipation of tax reduction make use of earning management, including delaying sales, taking unusual income-decreasing discretionary accruals, and so on, which leads to lower income in higher tax rate period. We find that private enterprises have more attention to reduce earning in the higher tax rate period than state-owned enterprises (SOEs), indicating that the ownership has effect on the extent of earning management. Moreover, under the specific regulations in Chinese stock market, we find that for those listed companies with negative net profit in the previous year, the priority is how to reverse losses rather than tax saving.